1979
DOI: 10.1212/wnl.29.4.490
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography and pure motor hemiparesis

Abstract: Computed tomography (CT) was abnormal in 75% of 33 patients with pure motor hemiparesis (PMH). In 13 cases, lesions were detected in the capsular region; 10 were consistent with infarction, and 3 were of increased density consistent with hemorrhage. Seven had other vascular disorders, and four had nonvascular conditions. Of 20 patients with PMH with normal electroencephalogram (EEG), isotope scan, and cerebrospinal fluid, 11 had CT evidence of a lesion in the internal capsule-corona radiata region. In patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
2

Year Published

1980
1980
1990
1990

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 0 publications
1
35
2
Order By: Relevance
“…1 We attribute the low percentage of positive correlation between CT and lacunes to the small size of the brain lesions (<32 mm) and to the effect of the bony artifacts that, in the posterior fossa, frequently interfere with the visualization of small brain stem lesions. 43 - 44 Associated lacunes existed in 11% of our patients, a figure lower than the 38% reported by others. 45 The existence of associated vascular lesions in patients with symptomatic lacunes is not surprising as several clinicopathologic studies have shown that most lacunes are multiple and that many are asymptomatic.…”
Section: Discussioncontrasting
confidence: 79%
“…1 We attribute the low percentage of positive correlation between CT and lacunes to the small size of the brain lesions (<32 mm) and to the effect of the bony artifacts that, in the posterior fossa, frequently interfere with the visualization of small brain stem lesions. 43 - 44 Associated lacunes existed in 11% of our patients, a figure lower than the 38% reported by others. 45 The existence of associated vascular lesions in patients with symptomatic lacunes is not surprising as several clinicopathologic studies have shown that most lacunes are multiple and that many are asymptomatic.…”
Section: Discussioncontrasting
confidence: 79%
“…In this present study hypertension was less frequently found and angiography revealed evidence of atheromatous thrombo-embolism in several cases. That the same clinical picture of a small deep infarct can be seen with small vessel disease in the hypertensive (Fisher, 1969) and with disease of the carotid and middle cerebral artery (Weisberg, 1979) is clearly important in the management of such patients. The clinical picture of a lacunar stroke should perhaps not deter investigation by angiography if bruits or non-invasive investigation suggests the presence of neck vessel disease.…”
Section: Discussionmentioning
confidence: 91%
“…The site of the lesion does not precisely determine its pathogenesis as infarction, hemorrhage, infection, 23 or neoplasm. 24 CT has established that small intracerebral hemorrhages 25 - 26 and large ischemic infarcts 27 can cause "lacunar syndromes." The cause(s) of "lacunar syndromes" have strayed so far from stroke as to include cysticercosis.…”
mentioning
confidence: 99%